1999
DOI: 10.1007/s004250050640
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of adenosine 5′-diphosphoglucose pyrophosphorylase to the control of starch synthesis in potato tubers

Abstract: The aim of this work was to investigate the extent to which starch synthesis in potato (Solanum tuberosum L.) tubers is controlled by the activity of ADPglucose pyrophosphorylase (EC 2.7.7.27; AGPase). In order to do this, fluxes of carbohydrate metabolism were measured in tubers that had reduced AGPase activity as a result of the expression of a cDNA encoding the B subunit in the antisense orientation. Reduction in AGPase activity led to a reduction in starch accumulation, and an increase in sucrose accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 23 publications
16
73
0
Order By: Relevance
“…It is known for sure [10] that biosynthesis and deposition of storage starch in potato tubers involve at least four main groups of enzymes: ADP glucose pyrophosphorylases (AGP), starch synthases (SS), enzymes catalyzing the branching of glucan chains (BE), and debranching enzymes (DBE). AGP cata lyze production of ADP glucose (this reaction restricts the total rate of starch biosynthesis in tubers) [24]. Because expression of rolB and rolC genes did not induce considerable changes in the total content of starch in tubers of transformed plants (Table 1), one can assume that these transgenes do not affect the ini tial stage of starch biosynthesis associated with AGP activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is known for sure [10] that biosynthesis and deposition of storage starch in potato tubers involve at least four main groups of enzymes: ADP glucose pyrophosphorylases (AGP), starch synthases (SS), enzymes catalyzing the branching of glucan chains (BE), and debranching enzymes (DBE). AGP cata lyze production of ADP glucose (this reaction restricts the total rate of starch biosynthesis in tubers) [24]. Because expression of rolB and rolC genes did not induce considerable changes in the total content of starch in tubers of transformed plants (Table 1), one can assume that these transgenes do not affect the ini tial stage of starch biosynthesis associated with AGP activity.…”
Section: Discussionmentioning
confidence: 99%
“…5B). ADP-Glc is formed by AGPase, an enzyme representing an important control step in starch synthesis (Sweetlove et al, 1999) and allosterically affected by the 3-PGA-inorganic phosphate ratio (Preiss 1988;Crevillén et al, 2003). The allosteric stimulation by high phosphoglyceric acid/ inorganic phosphate was also evident in the oilseed rape embryo (Supplemental Fig.…”
Section: Control Of Carbon Partitioning Between Lipid and Starchmentioning
confidence: 94%
“…Different studies concerning starch metabolism in potato and tomato have suggested that AGPase activity plays an important role in regulation (Geigenberger et al, 1999;Sweetlove et al, 1999;Geigenberger, 2011). AGPase activity is known to be modulated via several different mechanisms.…”
Section: Effects Of Cytosolic Pepck and Plastidic Nadp-me On Starch Bmentioning
confidence: 99%